SrTiO3-coated ReS2 core-sheath composite photocatalytic material as well as preparation method and application thereof
By constructing SrTiO3@ReS2 core-sheath composite photocatalytic material, the light excitation range is broadened and electron-hole separation is promoted, which solves the problem of insufficient absorption capacity of strontium titanate photocatalyst and improves the photocatalytic hydrogen production performance.
Patent Information
- Application Number
- CN202510515043.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2025-09-19
AI Technical Summary
The existing strontium titanate photocatalyst has insufficient photocatalytic hydrogen production performance due to its wide band gap, which limits its ability to absorb visible light.
A SrTiO3@ReS2 core-sheath composite photocatalytic material was constructed, in which ReS2 served as a shell covering the SrTiO3 core to form a type II heterojunction, broadening the photoexcitation range and promoting electron-hole separation.
It improves the photocatalytic activity and solar energy utilization, enhances the photogenerated carrier utilization and reaction active sites of the photocatalyst, and improves the hydrogen generation efficiency.
Smart Images

Figure CN120662336A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries and relates to a SrTiO3@ReS2 core-sheath composite photocatalytic material and a preparation method and application thereof. Background Art
[0002] As the global population and economy continue to grow, humanity's demand for energy continues to climb to unprecedented heights. The combustion of traditional fossil fuels has led to a series of increasingly severe problems, such as global warming, energy shortages, and environmental degradation, posing serious challenges to human health and economic development. To address these challenges, scientists are actively researching green and renewable energy sources as alternatives to fossil fuels. Among the many renewable energy sources, hydrogen is considered key to achieving energy transformation due to its widespread availability, clean and pollution-free operation, ease of storage and recycling, and high energy density. However, traditional hydrogen production methods, such as water electrolysis, rely on fossil fuels for power generation, resulting in high energy consumption and low efficiency. This has prompted scientists to search for more efficient and cost-effective hydrogen production technologies. Against this backdrop, photocatalytic hydrogen production has attracted considerable attention due to its environmentally friendly and cost-effective nature. By utilizing reliable photocatalysts, this technology can directly convert solar energy into chemical energy, achieving efficient conversion from primary energy to target products without relying on fossil fuels.
[0003] The core of photocatalytic hydrogen production technology lies in the development of efficient photocatalysts. Strontium titanate (SrTiO3), as a commonly used photocatalyst, is widely used due to its suitable band edge position and good photochemical stability. However, its wide band gap (3.2eV) limits its ability to absorb visible light, thereby affecting the hydrogen production performance. Despite this, various means are used to improve the performance of strontium titanate, such as ion doping, surface modification or the formation of heterostructures, in order to improve its photocatalytic activity. In addition, in addition to strontium titanate, many other types of semiconductor materials have also been explored for photocatalytic hydrogen production, such as cadmium sulfide (CdS), zinc oxide (ZnO), etc. Each material has its own unique advantages and limitations. Summary of the Invention
[0004] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and propose a SrTiO3@ReS2 core-sheath composite photocatalytic material, which broadens the light excitation range of the material, successfully constructs a type II heterojunction, and thus promotes the improvement of photocatalytic hydrogen production performance.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A SrTiO3@ReS2 core-sheath composite photocatalytic material, wherein the surface sheath of the catalytic material is ReS2 and the inner core is SrTiO3, wherein the molar ratio of ReS2 to SrTiO3 is 0.1-1:1.
[0007] The present invention constructs an innovative core-sheath structure by using ReS2 and SrTiO3 in a specific molar ratio of 0.1-1:1, in which ReS2 acts as a shell wrapped around the SrTiO3 core. This unique design is not just for physical combination, but is based on a deep understanding and clever use of the properties of the two materials. As a wide-bandgap semiconductor material, SrTiO3, although it has good photochemical stability and certain photocatalytic activity, its wide bandgap limits its effective absorption capacity of visible light, which greatly restricts its efficiency in solar energy conversion applications. In contrast, ReS2 has a narrower bandgap and can effectively absorb the visible light portion of the solar spectrum. Therefore, combining the two can significantly broaden the overall photoexcitation range of the composite material.
[0008] This core-sheath structure design successfully constructs a type II heterojunction. A key advantage of a type II heterojunction is that it promotes the spatial separation of electrons and holes, reducing their recombination probability, thereby improving the effective utilization of photogenerated carriers. Specifically, under light conditions, electrons in the valence band of SrTiO3 are excited to the conduction band and then rapidly transferred to the conduction band of ReS2, while holes remain in the valence band of SrTiO3. This electron-hole pair separation mechanism effectively extends the carrier lifetime, allowing more electrons and holes to participate in surface reactions, thereby enhancing the overall photocatalytic activity. The presence of the ReS2 shell not only expands the material's light absorption range but also provides additional active sites for the catalytic reaction. These active sites are crucial for the generation of products such as hydrogen because they can reduce the activation energy of the reaction and accelerate the reaction rate. At the same time, the synergistic effect between ReS2 and SrTiO3 also helps to improve the material's stability, enabling it to maintain efficient photocatalytic performance under a wider range of environments.
[0009] The present invention also provides a method for preparing the above-mentioned SrTiO3@ReS2 core-sheath composite photocatalytic material, the method comprising the following steps:
[0010] S1. High-temperature treatment of strontium titanate nanofibers in an NH3 atmosphere to obtain a powder, and uniformly dispersing the powder in water to obtain a dispersion A;
[0011] S2, dissolving ammonium perrhenate, thiourea, and hydroxylamine hydrochloride in water to obtain dispersion B;
[0012] S3. Dispersion A and dispersion B are mixed and stirred evenly, and then subjected to hydrothermal reaction. Finally, the mixture is centrifugally dried to obtain a SrTiO3@ReS2 core-sheath composite photocatalytic material.
[0013] In the above-mentioned method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material, step S1 is high temperature treatment at 3-8℃·min -l The temperature is raised to 500-700℃ at a rate of 100-200℃, and then kept at this temperature for 0.5-5h. NH3 is continuously introduced during the high temperature treatment process, and the NH3 flow rate is 50-150mL·min -l .
[0014] In the above-mentioned method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material, the mass ratio of ammonium perrhenate, thiourea, and hydroxylamine hydrochloride in step S2 is (1.5-2.5): (2.5-3.0):1.
[0015] In the above-mentioned method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material, the hydrothermal reaction temperature is 150-250°C and the reaction time is 5-48 hours.
[0016] In the above-mentioned method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material, the method for preparing strontium titanate nanofibers includes the following steps:
[0017] S1. Evenly mix acetic acid and strontium acetate until the strontium acetate is completely dissolved, then add tetrabutyl titanate and continue stirring to obtain solution A;
[0018] S2. Fully stirring 2-methoxyethanol, water, and polyvinylpyrrolidone to obtain solution B;
[0019] S3, mixing solution A and solution B and then subjecting them to high temperature treatment to obtain a spinning solution;
[0020] S4, electrospinning the spinning solution to obtain a strontium titanate precursor;
[0021] S5. The strontium titanate precursor is first dried and then subjected to high-temperature annealing to obtain porous strontium titanate nanofibers.
[0022] Preferably, the mass ratio of acetic acid to strontium acetate in step S1 is (3-8):1.
[0023] More preferably, in step S1, the molar ratio of the titanium element in tetrabutyl titanate to the strontium element in strontium acetate is 1:(0.5-1.5).
[0024] In the above-mentioned method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material, the mass ratio of 2-methoxyethanol, water and polyvinylpyrrolidone in step S2 is (5-10): (1-5): (1-5).
[0025] In the above-mentioned method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material, the mass ratio of solution A to solution B in step S3 is 1:(1-1.5).
[0026] The high temperature treatment temperature in step S3 is 35-45°C and the time is 3-8 hours.
[0027] Preferably, the electrospinning process parameters in step 4 are as follows: spinning voltage is 20kV-26kV, receiving distance is 18-25cm, spinning temperature is 20-30°C, humidity is 10-30%, and inner core spinning solution advancing speed is 0.15-0.3mL / h.
[0028] In the above-mentioned method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material, step S5 is a drying treatment in which the temperature is raised to 150-250°C at a rate of 1-5°C / min and kept warm for 1-5 hours; a high-temperature annealing treatment is performed in which the temperature is raised to 700-800°C at a rate of 1-5°C / min and annealed for 1-3 hours.
[0029] An application of the above-mentioned SrTiO3@ReS2 core-sheath composite photocatalytic material or the SrTiO3@ReS2 core-sheath composite photocatalytic material prepared by the above-mentioned preparation method in photocatalytic oxidation technology.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The present invention utilizes a specific molar ratio of ReS2 to SrTiO3 to create a core-sheath structure, with the ReS2 acting as a shell covering a SrTiO3 core. This design not only broadens the material's photoexcitation range, overcoming the narrow absorption range associated with the wide bandgap of SrTiO3 alone, but also successfully creates a type II heterojunction, effectively promoting the separation of electron-hole pairs and reducing their recombination probability, further enhancing photocatalytic activity.
[0032] 2. The preparation method of the present invention includes a series of carefully designed steps, from high-temperature treatment of strontium titanate nanofibers to the formation of the final SrTiO3@ReS2 core-sheath composite photocatalytic material. In particular, during the high-temperature treatment process in an ammonia atmosphere, the high-quality conversion of the precursor material is ensured by precisely controlling the heating rate and holding time; while in the hydrothermal reaction stage, the morphology and performance of the product are optimized by adjusting the temperature, time, and raw material ratio. In addition, strontium acetate is mixed with tetrabutyl titanate and then electrospun, followed by drying and high-temperature annealing to obtain strontium titanate nanofibers with a porous structure, providing an ideal substrate for the subsequent successful loading of ReS2.
[0033] 3. The SrTiO3@ReS2 core-sheath composite photocatalytic material of the present invention has broad application prospects, particularly in the field of photocatalytic oxidation technology. Its core advantage lies in its ability to provide a high-density interface between the co-catalyst and the photocatalyst, as well as abundant edge active sites, which greatly promote the efficient H2 evolution. Furthermore, due to the narrow band gap of ReS2, it can effectively absorb visible light, compensating for the limitation of SrTiO3 that only absorbs ultraviolet light. This allows the entire composite material to operate across a wider range of the solar spectrum, thereby improving the utilization rate of solar energy.
[0034] 4. The SrTiO3@ReS2 core-sheath composite photocatalytic material of this invention not only provides new ideas and technical means for addressing the current energy crisis and environmental pollution, but also promotes the development of renewable energy conversion technology through the development of high-performance photocatalytic materials. It demonstrates significant potential and value in key application areas such as sewage treatment, air purification, antibacterial and antiviral treatment, and photocatalytic water splitting for hydrogen production. Therefore, this invention is of great significance for promoting sustainable development and achieving the clean energy transition. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a flow chart for the preparation of the core-sheath structured SrTiO3@ReS2 composite photocatalyst of the present invention.
[0036] Figure 2 Figure 2 shows the SEM images of the undoped SrTiO3 nanofibers of Example 2 and the SrTiO3@ReS2 of Example 1, as well as the Re, S, Sr, and Ti element mapping diagrams. a) SEM image of the undoped SrTiO3 nanofibers, b) the corresponding Re, S, Sr, and Ti element mapping diagrams, c) SEM image of the nitrogen-doped SrTiO3 nanofibers, and d) the corresponding Re, S, Sr, and Ti element mapping diagrams.
[0037] Figure 3 1-7 are XRD patterns of the composite materials of Examples 1-7.
[0038] Figure 4 Figure 3 shows the X-ray photoelectron spectroscopy (XPS) patterns of the nitrogen-doped SrTiO3 nanofibers of Example 3 and the SrTiO3@ReS2 of Example 1. a is the full XPS spectrum, b is the corresponding high-resolution Ti 2p spectrum, c is the corresponding high-resolution O1s spectrum, d is the corresponding high-resolution Sr 3d spectrum, e is the corresponding high-resolution N1s spectrum, f is the high-resolution Re4f spectrum of the nitrogen-doped SrTiO3 nanofibers, and g is the high-resolution S2p spectrum of the nitrogen-doped SrTiO3 nanofibers.
[0039] Figure 5 The kinetic curves of photocatalytic hydrogen production of the composite materials of Examples 1-7 are shown in Figures a and b. The kinetic curves of photocatalytic hydrogen evolution of pure SrTiO3(ST), tSrTiO3(tST), and tST(3) / RS(2-10) are shown in Figures b and c.
[0040] Figure 6 UV-visible absorption spectra of SrTiO3@ReS2 of Examples 1-7.
[0041] Figure 7 This is a diagram showing the mechanism of photocatalytic hydrogen production of the SrTiO3@ReS2 heterojunction in Example 1. DETAILED DESCRIPTION
[0042] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0043] Example 1:
[0044] according to Figure 1 The process shown is to prepare SrTiO3@ReS2 core-sheath composite photocatalytic material;
[0045] S1. Preparation of strontium titanate precursor fiber film: Dissolve 0.515 g of strontium acetate in 2.5 mL of glacial acetic acid and stir for 0.5 hour. Then add 0.85 g of tetrabutyl titanate and stir for 1 hour. This solution is designated A. Dissolve 0.602 g of polyvinyl pyrrolidone in 1.5 mL of 2-methoxyethanol and 3 mL of ultrapure water and stir for 1 hour. This solution is designated B. The clarified A and B solutions are mixed and stirred for 12 hours to obtain a polymer strontium titanate precursor solution for electrospinning.
[0046] S2. Placing the polymer strontium titanate precursor solution into a propulsion pump, selecting the spinning voltage, receiving distance, spinning temperature and humidity, adjusting the propulsion speed of the propulsion pump, and performing electrospinning to obtain a precursor composite fiber; during electrospinning, a voltage of 20 kV is applied between the needle and the receiving plate, the spinning solution ejection speed is 0.057 mm / min (0.6 mL / h), the ambient temperature is above 30° C., and the humidity is below 25%;
[0047] S3. The precursor composite fiber prepared above is placed in a muffle furnace for calcination to remove the polymer template and promote the nucleation, crystallization and sintering of the oxide. The specific sintering process is as follows: heating to 200° C. at a heating rate of 2° C. / min, holding for 2 hours, then heating to 750° C. at a heating rate of 2° C. / min, holding for 3 hours, to obtain strontium titanate nanofibers with a porous structure. At the same time, the elements on the fiber are uniformly distributed during the sol-gel process, and the strontium titanate fibers prepared by sintering have good crystallinity.
[0048] S4. Transfer 100 mg of untreated SrTiO3 nanofibers to an uncovered alumina boat, place it in a tube furnace, and pass ammonia gas. When the gas flow is stable, heat it at 5°C / min. -l The temperature was raised to 600 °C at a rate of 100 mL / min and maintained for 3 hours. The continuous flow rate of nitrogen doping was 100 mL / min. -l After nitrogen doping, tST light grey powder was obtained;
[0049] S4. Place 100 mg of strontium titanate nanofiber powder in 20 mL of ultrapure water and sonicate for 30 minutes until the powder is completely dispersed in dispersion A. Dissolve 84 mg of ammonium perrhenate, 108.8 mg of thiourea, and 42 mg of hydroxylamine hydrochloride in 10 mL of ultrapure water to obtain dispersion B. Mix dispersions A and B and pour them into a 50 mL PPL hydrothermal liner and hydrothermally treat at 220°C for 24 hours. Centrifuge the solution at 8000 rpm for 5 minutes, take the precipitate, wash it twice with ultrapure water and ethanol, and centrifuge it separately. Place the precipitate in a drying oven at 70°C for 8 hours to fully dry it to obtain a tSrTiO3 / ReS2 composite material, in which the molar ratio of ReS2 to SrTiO3 is 0.58:1.
[0050] Example 2:
[0051] S1. Preparation of strontium titanate precursor fiber film: Dissolve 0.515 g of strontium acetate in 2.5 mL of glacial acetic acid and stir for 0.5 hour. Then add 0.85 g of tetrabutyl titanate and stir for 1 hour. This solution is designated A. Dissolve 0.602 g of polyvinyl pyrrolidone in 1.5 mL of 2-methoxyethanol and 3 mL of ultrapure water and stir for 1 hour. This solution is designated B. The clarified A and B solutions are mixed and stirred for 12 hours to obtain a polymer strontium titanate precursor solution for electrospinning.
[0052] S2. Placing the polymer strontium titanate precursor solution into a propulsion pump, selecting the spinning voltage, receiving distance, spinning temperature and humidity, adjusting the propulsion speed of the propulsion pump, and performing electrospinning to obtain a precursor composite fiber; during electrospinning, a voltage of 20 kV is applied between the needle and the receiving plate, the spinning solution ejection speed is 0.057 mm / min (0.6 mL / h), the ambient temperature is above 30° C., and the humidity is below 25%;
[0053] S3. The precursor composite fiber prepared above is placed in a muffle furnace for calcination to remove the polymer template and promote the nucleation, crystallization and sintering of the oxide. The specific sintering system is: heating rate is 2°C / min, heating to 200°C, keeping warm for 2 hours, then heating to 750°C at 2°C / min, keeping warm for 3 hours, and obtaining strontium titanate nanofibers with a porous structure, denoted as ST.
[0054] Example 3:
[0055] S1. Preparation of strontium titanate precursor fiber film: Dissolve 0.515 g of strontium acetate in 2.5 mL of glacial acetic acid and stir for 0.5 hour. Then add 0.85 g of tetrabutyl titanate and stir for 1 hour. This solution is designated A. Dissolve 0.602 g of polyvinyl pyrrolidone in 1.5 mL of 2-methoxyethanol and 3 mL of ultrapure water and stir for 1 hour. This solution is designated B. The clarified A and B solutions are mixed and stirred for 12 hours to obtain a polymer strontium titanate precursor solution for electrospinning.
[0056] S2. Placing the polymer strontium titanate precursor solution into a propulsion pump, selecting the spinning voltage, receiving distance, spinning temperature and humidity, adjusting the propulsion speed of the propulsion pump, and performing electrospinning to obtain a precursor composite fiber; during electrospinning, a voltage of 20 kV is applied between the needle and the receiving plate, the spinning solution ejection speed is 0.057 mm / min (0.6 mL / h), the ambient temperature is above 30° C., and the humidity is below 25%;
[0057] S3. The precursor composite fiber prepared above is placed in a muffle furnace for calcination to remove the polymer template and promote the nucleation, crystallization and sintering of the oxide. The specific sintering system is: heating rate is 2°C / min, heating to 200°C, keeping warm for 2 hours, then heating to 750°C at 2°C / min, keeping warm for 3 hours, and thus strontium titanate nanofibers with a porous structure are obtained.
[0058] S4. Transfer 100 mg of untreated SrTiO3 nanofibers to an uncovered alumina porcelain boat and place it in a tube furnace with ammonia gas. After the gas flow stabilizes, heat the mixture at 5°C / min. -l The temperature was raised to 600 °C at a rate of 100 mL / min and maintained for 3 hours. The continuous flow rate of nitrogen doping was 100 mL / min. -l, and the light grey powder obtained after nitrogen doping treatment was recorded as tST.
[0059] Example 4:
[0060] The only difference from Example 1 is that the molar ratio of ReS2 to SrTiO3 in the prepared tSrTiO3 / ReS2 composite material is 0.14:1, which is recorded as tST(3) / RS2.
[0061] Example 5:
[0062] The only difference from Example 1 is that the molar ratio of ReS2 to SrTiO3 in the prepared tSrTiO3 / ReS2 composite material is 0.29:1, which is recorded as tST(3) / RS4.
[0063] Example 6:
[0064] The only difference from Example 1 is that the molar ratio of ReS2 to SrTiO3 in the prepared tSrTiO3 / ReS2 composite material is 0.43:1, which is recorded as tST(3) / RS6.
[0065] Example 7:
[0066] The only difference from Example 1 is that the molar ratio of ReS2 to SrTiO3 in the prepared tSrTiO3 / ReS2 composite material is 0.72:1, which is recorded as tST(3) / RS10.
[0067] Figure 2 The SEM images of the untreated SrTiO3 nanofibers in Example 2 and the SrTiO3@ReS2 in Example 1, as well as the Re, S, Sr, and Ti element mapping diagrams are shown. Through SEM observation, it can be clearly seen that ReS2 has successfully grown in situ on the surface of the treated SrTiO3 nanofibers. Figure 2 (a) Compared with pure SrTiO3 nanofibers, Figure 2 The morphology of the composite material in (c) is obviously different, with obvious granular material growth on the surface. In addition, except for Sr and O elements, the EDS image ( Figure 2 Re and S elements can also be clearly seen in (d)), which provides an important basis for a series of subsequent characterizations, performance tests and mechanism explanations.
[0068] Figure 3The XRD patterns of the untreated SrTiO3 nanofibers from Example 2 and the SrTiO3@ReS2 from Example 1 are shown. As can be seen from the figure, the Example 2 sample is consistent with the SrTiO3 standard card, indicating that the calcination treatment has converted the organic precursor solution required for the electrospinning process into a pure SrTiO3 sample. With the incorporation of ReS2, corresponding diffraction peaks can be seen.
[0069] Figure 4 The X-ray photoelectron spectroscopy (XPS) diagram of the untreated SrTiO3 nanofibers of Example 2 and the SrTiO3@ReS2 of Example 1. The element binding energy of carbon impurities at 284.8 eV was calibrated using C1s. Figure 4 The XPS full spectrum of (a) shows that the composite material shows obvious presence of Ti, O, Sr, and N, and Figure 1-2 The EDS results in the high-resolution Ti 2pXPS spectrum (such as Figure 4 In (b), the two characteristic peaks observed are from Ti 2p 1 / 2 and Ti 2p 3 / 2 orbitals, located at 463.9eV and 458.2eV respectively. In the high-resolution O1s XPS spectrum (such as Figure 4 (c)), the characteristic peak of O 1s is located at 529.2eV. In the high-resolution Sr 3d XPS spectrum (such as Figure 4 (d)) comes from Sr 3d 3 / 2 and Sr 3d 5 / 2 The characteristic peaks of the orbital are located at 134.3eV and 132.7eV. After being treated in a high temperature ammonia atmosphere, Figure 4 As shown in (e), the sample exhibits a characteristic peak originating from N1s at 399.9 eV. Clearly, the binding energies of the various elements (Ti, O, S, and N) in the composite material bound to ReS2 have shifted positively, demonstrating a shift in the electron cloud caused by composite synthesis, namely, electron transfer from SrTiO3 to ReS2. Figure 4 (f) and Figure 4 The Re 4f and S2p in (g) show characteristic peaks centered at 44.2 eV, 41.8 eV and 169.6 eV, 162.6 eV, which directly indicates that the hydrothermal process successfully loaded ReS2 on the SrTiO3 surface.
[0070] Figure 5 The kinetic curves of photocatalytic hydrogen production from pure SrTiO3 in Example 2, SrTiO3 heat-treated with NH3 in Example 3, and the SrTiO3 / ReS2 composite material prepared in Example 1 are shown. The experimental results show that the in-situ hydrothermal growth of ReS2 on SrTiO3 heat-treated with NH3 can significantly improve the hydrogen evolution efficiency. Figure 5 (a) shows the photocatalytic hydrogen production rate diagram. It can be found that with the increase of Re and S dosage, the hydrogen production rate of the composite sample shows an increasing trend. It reaches a peak at tST(3) / RS8, with a hydrogen production rate of 562.6 μmol·g -1 ·h -1 However, when the input of Re and S elements continued to increase, the hydrogen production rate decreased to 272.4 μmol·g -1 ·h -1 (tST(3) / RS10), which indicates that the thick ReS2 nanoparticle layer and the breakage of nanofibers will affect the photocatalytic hydrogen production performance of the material. It is worth noting that the hydrogen production rate of tST(3) / RS8 is 2.8 times that of ST and 2.6 times that of tST.
[0071] Figure 6 This is the UV-visible absorption spectrum of SrTiO3@ReS2 from Example 1. Observation of the spectrum reveals a significant red-shift in the composite's absorption with increasing amounts of hydrothermally grown ReS2. The absorption intensity in the visible light range (400-780 nm) significantly increases, approaching that of pure ReS2. This figure demonstrates that the SrTiO3 / ReS2 nanoheterojunction composite broadens its light absorption range, contributing to improved photocatalytic performance.
[0072] Figure 7 The diagram shows the mechanism of photocatalytic hydrogen production of the SrTiO3@ReS2 heterojunction of Example 1. Under illumination conditions, the photogenerated electrons generated at the valence band (VB) of SrTiO3 and ReS2 respectively transition to the conduction band (CB), leaving photogenerated holes at the VB. Since the band gap width of ReS2 is much smaller than that of SrTiO3, it is easier to be excited to form photogenerated "electron-hole" pairs under visible light irradiation conditions. Driven by the difference in the band gap positions of SrTiO3 and ReS2, the close contact interface between them enables the photogenerated electrons to be quickly transferred to the CB of SrTiO3, while the photogenerated holes can be transferred to the VB of ReS2, thereby forming a Z-type heterojunction. On the surface of the composite material, the photogenerated electrons and H in water +Combined with the photocatalytic reaction, a reduction reaction occurs to generate hydrogen (H2), while the photogenerated holes undergo an oxidation reaction with the sacrificial agent and are consumed, thus avoiding the recombination of photogenerated carriers. In addition, the narrow band gap of ReS2 makes up for the small absorption range of the wide-bandgap semiconductor catalyst SrTiO3, and also provides abundant edge active sites for the composite material, which is also conducive to the precipitation of H2. Through the above process, the photocatalytic hydrogen evolution ability of the SrTiO3 heterojunction composite material is significantly enhanced. The enhanced photon absorption ability of the SrTiO3 / ReS2 composite material is combined with the efficient charge transfer, which makes the SrTiO3 heterojunction composite material exhibit higher photocatalytic hydrogen evolution activity under light conditions.
[0073] In summary, the present invention employs a specific molar ratio of ReS2 to SrTiO3 to create a core-sheath structure, with the ReS2 acting as a shell covering a SrTiO3 core. This design not only broadens the material's photoexcitation range, overcoming the narrow absorption range inherent to the wide bandgap of SrTiO3 alone, but also successfully constructs a type II heterojunction, effectively improving the separation efficiency of electron-hole pairs, reducing their recombination probability, and further enhancing photocatalytic activity.
[0074] The parts of the embodiment herein that are not exhaustive of the midpoint values of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the embodiments listed or not listed in the solutions of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.
[0075] The technical means disclosed in the solutions of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical solutions composed of any combination of the above technical features. The above is a specific embodiment of the present invention. It should be noted that for those skilled in the art, various improvements and modifications can be made without departing from the principles of the present invention, and such improvements and modifications are also considered to be within the scope of protection of the present invention.
[0076] The specific embodiments described herein are merely illustrative of the spirit of the present invention. Persons skilled in the art may make various modifications, additions, or substitutions to the described specific embodiments without departing from the spirit of the present invention or exceeding the scope of the appended claims.
Claims
1. A SrTiO3@ReS2 core-sheath composite photocatalytic material, characterized in that: The surface sheath of the catalytic material is ReS2, and the inner core is SrTiO3, wherein the molar ratio of ReS2 to SrTiO3 is 0.1-1:
1.
2. A method for preparing the SrTiO3@ReS2 core-sheath composite photocatalytic material as claimed in claim 1, characterized in that: The method comprises the following steps: S1. High-temperature treatment of strontium titanate nanofibers in an NH3 atmosphere to obtain a powder, and uniformly dispersing the powder in water to obtain a dispersion A; S2, dissolving ammonium perrhenate, thiourea, and hydroxylamine hydrochloride in water to obtain dispersion B; S3. Dispersion A and dispersion B are mixed and stirred evenly, and then subjected to hydrothermal reaction. Finally, the mixture is centrifugally dried to obtain a SrTiO3@ReS2 core-sheath composite photocatalytic material.
3. The method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material according to claim 1, characterized in that: Step S1: high temperature treatment at 3-8℃·min -l The temperature is raised to 500-700℃ at a rate of 100-200℃, and then kept at this temperature for 0.5-5h. NH3 is continuously introduced during the high temperature treatment process, and the NH3 flow rate is 50-150mL·min -l .
4. The method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material according to claim 1, characterized in that: It is characterized by: In step S2, the mass ratio of ammonium perrhenate, thiourea, and hydroxylamine hydrochloride is (1.5-2.5):(2.5-3.0):
1.
5. The method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material according to claim 1, characterized in that: The hydrothermal reaction temperature is 150-250°C and the reaction time is 5-48h.
6. The method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material according to claim 1, characterized in that: The preparation method of strontium titanate nanofibers comprises the following steps: S1. Evenly mix acetic acid and strontium acetate until the strontium acetate is completely dissolved, then add tetrabutyl titanate and continue stirring to obtain solution A; S2. Fully stirring 2-methoxyethanol, water, and polyvinylpyrrolidone to obtain solution B; S3, mixing solution A and solution B and then subjecting them to high temperature treatment to obtain a spinning solution; S4, electrospinning the spinning solution to obtain a strontium titanate precursor; S5. The strontium titanate precursor is first dried and then subjected to high-temperature annealing to obtain porous strontium titanate nanofibers.
7. The method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material according to claim 6, characterized in that: The mass ratio of 2-methoxyethanol, water and polyvinylpyrrolidone in step S2 is (5-10): (1-5): (1-5).
8. The method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material according to claim 6, characterized in that: In step S3, the mass ratio of solution A to solution B is 1:(1-1.5).
9. The method for preparing a SrTiO3@ReS2 core-sheath composite photocatalytic material according to claim 6, characterized in that: Step S5: Drying treatment: Raise the temperature to 150-250°C at a rate of 1-5°C / min and keep it for 1-5 hours; High temperature annealing treatment: Raise the temperature to 700-800°C at a rate of 1-5°C / min and anneal for 1-3 hours.
10. Use of the SrTiO3@ReS2 core-sheath composite photocatalytic material according to claim 1 or the SrTiO3@ReS2 core-sheath composite photocatalytic material prepared by the preparation method according to any one of claims 2 to 9 in photocatalytic oxidation technology.